2006
DOI: 10.1002/aqc.737
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in the fish assemblage of the Laja River, Guanajuato, central Mexico

Abstract: ABSTRACT1. The structure and composition of fish communities in rivers of central Mexico have been altered as a result of water over-exploitation, habitat fragmentation, introduction of exotic species, and pollution. However, the specific pattern and degree of change are poorly documented.2. Long-term information from the Laja River (Guanajuato, Mexico) in the Lerma River basin was used to explore trends in fish species richness and community composition (species origin, trophic niche, tolerance, and preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 25 publications
0
44
0
4
Order By: Relevance
“…Historical research on changes in ecosystem elements and processes help understand the effects of anthropogenic threats and provide specific information that can be used to reduce further ecosystem degradation (Karr, 1981;Mercado-Silva et al, 2006). Data about long-term changes can aid in developing monitoring strategies and future conservation efforts (Olden & Poff, 2005;Mercado-Silva et al, 2006). Although anthropic effects on the watershed and the water quality of Lago de Pátzcuaro are relatively well documented, this study represents the first effort to understand the long-term changes of the fish assemblages in this lake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Historical research on changes in ecosystem elements and processes help understand the effects of anthropogenic threats and provide specific information that can be used to reduce further ecosystem degradation (Karr, 1981;Mercado-Silva et al, 2006). Data about long-term changes can aid in developing monitoring strategies and future conservation efforts (Olden & Poff, 2005;Mercado-Silva et al, 2006). Although anthropic effects on the watershed and the water quality of Lago de Pátzcuaro are relatively well documented, this study represents the first effort to understand the long-term changes of the fish assemblages in this lake.…”
Section: Discussionmentioning
confidence: 99%
“…For most records no information on sampling effort or gear type was available, and we had to assume that sampling efforts adequately sampled the entire fish community. Because of this limitation, only presence/absence data were considered for analysis following Mercado-Silva et al (2006).…”
Section: Study Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such pumping has become increasingly prevalent due to human populations growth in areas adjacent to karst aquifers. Currently, the Devils River is without extensive anthropogenic alterations, but increasing pressure for groundwater extraction from the Edwards Aquifer might threaten the future of the Devils River fish assemblage, similar to other streams altered by groundwater extraction (Mercado-Silva et al, 2006). This study demonstrated spring flows serve as refugia for spring-associated species during winter and summer months and maintain environmentally variable areas downstream for riverine species, which collectively support a diverse fish assemblage.…”
Section: Speciesmentioning
confidence: 78%
“…Similar patterns of human impact are occurring in lakes and rivers elsewhere in Mexico and in other tropical countries, and highlight the urgent need to implement habitat protection and enhancement in nearshore areas and to prevent exotic species introductions (Bence et al 2002, Bronte et al 2003, Mills et al 2003, Mercado-Silva et al 2006. The IBI provides a tool to quantify the effectiveness of such conservation measures.…”
Section: Discussionmentioning
confidence: 89%